Role of Ginkgolides in the Inflammatory Immune Response of Neurological Diseases: A Review of Current Literatures - Li, Chunrong; Liu, Kangding; Liu, Shan; Aerqin, Qiaolifan; Wu, Xiujuan (Frontiers in Systems Neuroscience, 2020)
The inflammatory immune response (IIR) is a physiological or excessive systemic response, induced by inflammatory immune cells according to changes in the internal and external environments. An excessive IIR is the pathological basis for the generation and development of neurological diseases. Ginkgolides are one of the important medicinal ingredients in Ginkgo biloba. Many studies have verified that ginkgolides have anti-platelet activating, anti-apoptotic, anti-oxidative, neurotrophic, and neuroimmunomodulatory effects. Inflammatory immunomodulation is mediated by inhibition of the mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathways. They also inhibit the platelet activating factor (PAF)-mediated signal transduction to attenuate the inflammatory response. Herein we reviewed the studies on the roles of ginkgolides in inflammatory immunomodulation and suggested its potential role in novel treatments for neurological diseases.